Efficient and Economical Allocation of Irrigation Water under a Changing Environment: a Stochastic Multi‐Objective Nonlinear Programming Model - Yan, Zehao; Li, Mo; Li, Zhong (Irrigation and drainage, 2021)
Water scarcity causes conflicts between natural resources and socio‐economic development which reinforces the need for optimal allocation of irrigation water resources. Irrigation water resource allocation is a complex problem due to various uncertainties in natural conditions. In this study, a stochastic multi‐objective nonlinear programming model is developed for irrigation water allocation under uncertainty. The model is capable of balancing the conflicting objectives of maximizing both net economic benefit (NEB) and irrigation water use efficiency (IWUE). Moreover, it can reflect the random nature of water availability, and provide alternative water allocation schemes in response to climate change. The applicability of the developed model is demonstrated by a case study in north‐west China. Trade‐offs between NEB and IWUE are presented. Irrigation water allocation schemes to cope with changing environments, including climate change and varying water availability, are also proposed. The results demonstrate that the developed model can generate solutions that save irrigation water while ensuring NEB. This model is a useful tool to support the formulation of optimized water resources management policies in a changing environment. Résumé La pénurie d'eau entraîne des conflits entre les ressources naturelles et le développement socio‐économique, ce qui renforce la nécessité d'une allocation optimale des ressources en eau d'irrigation. L'allocation des ressources en eau d'irrigation est un problème complexe en raison de diverses incertitudes dans les conditions naturelles. Dans cette étude, un modèle de programmation non linéaire multi‐objectif stochastique est développé pour l'allocation de l'eau d'irrigation sous incertitude. Le modèle est capable d'équilibrer les objectifs contradictoires de maximisation des avantages économiques nets (NEB) et de l'efficacité d'utilisation de l'eau d'irrigation (IWUE). De plus, il peut refléter la nature aléatoire de la disponibilité en l'eau et fournir des plans alternatifs d'allocation en l'eau en réponse au changement climatique. L'applicabilité du modèle développé est démontrée par une étude de cas dans le nord‐ouest de la Chine. Les compromis entre les NEB et l'IWUE sont présentés. Des plans d'allocation de l'eau d'irrigation pour faire face à l'évolution des environnements, notamment le changement climatique et la disponibilité variable de l'eau, sont également proposés. Les résultats démontrent que le modèle développé peut générer des solutions qui économisent l'eau d'irrigation tout en garantissant les NEB. Ce modèle est un outil utile pour soutenir la formulation de politiques optimisées de gestion des ressources en eau dans un environnement en mutation.